The future of coffee and cocoa agroforestry in a warmer Mesoamerica - Sousa, Kauê de; Zonneveld, Maarten van; Holmgren, M.; Kindt, Roeland; Ordoñez, J.C. (Springer, 2019)
Climate change threatens cofee production and the livelihoods of thousands of families in Mesoamerica that depend on it. Replacing cofee with cocoa and integrating trees in combined agroforestry systems to ameliorate abiotic stress are among the proposed alternatives to overcome this challenge. These two alternatives do not consider the vulnerability of cocoa and tree species commonly used in agroforestry plantations to future climate conditions. We assessed the suitability of these alternatives by identifying the potential changes in the distribution of cofee, cocoa and the 100 most common agroforestry trees found in Mesoamerica. Here we show that cocoa could potentially become an alternative in most of cofee vulnerable areas. Agroforestry with currently preferred tree species is highly vulnerable to future climate change. Transforming agroforestry systems by changing tree species composition may be the best approach to adapt most of the cofee and cocoa production areas. Our results stress the urgency for land use planning considering climate change efects and to assess new combinations of agroforestry species in cofee and cocoa plantations in Mesoamerica.